2006
DOI: 10.1177/1087054705286061
|View full text |Cite
|
Sign up to set email alerts
|

ADHD in College Students

Abstract: Future research using larger sample sizes, rigorous assessment criteria, and a longitudinal design is needed to better understand the psychological, academic, and neuropsychological functioning of college students with ADHD. Studies are also needed to elucidate the effects of pharmacological and nonpharmacological effects of treatment on the functioning of college students with this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(174 citation statements)
references
References 52 publications
5
160
0
9
Order By: Relevance
“…These results are not surprising, given the past research on the academic problems often encountered by college students with ADHD. These include lack of organizational skills, problems with focusing and sustaining attention, deficits in executive functions (Weyandt & DuPaul, 2006), and using ineffective academic coping strategies, including procrastination and poor organization (Turnock, Rosen, & Kaminski, 1998). Contrary to prior research, ADHD symptomatology was not related to social adjustment or GPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are not surprising, given the past research on the academic problems often encountered by college students with ADHD. These include lack of organizational skills, problems with focusing and sustaining attention, deficits in executive functions (Weyandt & DuPaul, 2006), and using ineffective academic coping strategies, including procrastination and poor organization (Turnock, Rosen, & Kaminski, 1998). Contrary to prior research, ADHD symptomatology was not related to social adjustment or GPA.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a cross-cultural study DuPaul et al (2001) administered the Young Adult Rating Scale to 1,209 college students from universities in the United States, Italy, and New Zealand and found that prevalence rates of self-reported symptoms that met diagnostic criteria in the Diagnostic and Statistical Manual of Mental Disorders (4th ed., or DSM-IV; American Psychiatric Association, 1994) ranged from 0% to 8.1%. Collectively, studies of this nature have revealed that approximately 2%-8% of college students report significant symptoms of ADHD, although the exact prevalence of those with a full diagnosis is unknown (Weyandt & DuPaul, 2006).…”
Section: Adhd Symptoms In Adolescence and Adulthoodmentioning
confidence: 99%
“…These drugs are widely used therapeutically. With rates of ADHD in the range of 4-7% among US college students using DSM criteria 4 , and stimulant medication the standard therapy, there are plenty of these drugs on campus to divert to enhancement use.…”
Section: Paths To Enhancementmentioning
confidence: 99%
“…Students with "hidden disabilities," which includes ADHD, have represented the greatest increase. Because these students don't have to report to disability offices it is difficult to determine the prevalence of ADHD, but the best estimate is that 25% of students getting disability services do so because of ADHD and that 2% to 8% of the undergraduate population "self-report" ADHD symptoms (Weyandt & DuPaul, 2006;Wolf, 2001). …”
Section: Academic Achievement Of College Students With Adhdmentioning
confidence: 99%
“…The first review to describe the general academic functioning of college students with ADHD appeared only a few years ago and summarized results from 23 studies (Weyandt & DuPaul, 2006). They found that ADHD-diagnosed college students did not differ in IQ from those without ADHD, and were able to meet the demands of college courses.…”
Section: Academic Achievement Of College Students With Adhdmentioning
confidence: 99%